Abstracts of the 2016 CSBBCS Annual Meeting. (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2016)
The article presents abstracts of studies on cognitive science including the association of focused attention on higher performance in creative tasks, the effect on magnitude judgments of cross-modal context and anchoring and the shift in conservative criterion leading to apparent or measured decline in sensitivity.